Population pharmacokinetics and pharmacodynamics of busulfan with GSTA1 polymorphisms in patients undergoing allogeneic hematopoietic stem cell transplantation. (September 2015) - Choi, Boyoon; Kim, Myeong Gyu; Han, Nayoung; Kim, Therasa; Ji, Eunhee; Park, Seonyang; Kim, In-Wha; Oh, Jung Mi
Aim: A population pharmacokinetic (PPK) analysis was conducted to describe the influence of GSTA1 polymorphisms on intravenous busulfan in adults undergoing allogeneic hematopoietic stem cell transplantation.Patients & methods: A PPK model was developed from 36 patients by a one-compartment model with first-order elimination.Results: The typical value of clearance and volume of distribution were 11.0 l/h and 42.4 l, respectively. Clearance decreased by 15% and area under the concentration-time curves (AUCs) increased with GSTA1 variants compared with wild-type (both p < 0.05). Subtherapeutic AUCs were seen only in wild-type patients.Conclusion: To our knowledge, this is the first PPK study to suggest that GSTA1 polymorphisms in adults are associated with busulfan PK.